Liesegang-Like Rings in Lactational Changes in the Breast - Mohd T. Islam; Joyce J. Ou; Katrine Hansen; Rochelle A. Simon; M. Ruhul Quddus (Hindawi Limited, 2012)
Liesagang-like rings (LR) are periodic structures with equally spaced radial striations formed by a process that involves diffusion, nucleation, flocculation or precipitation, and supersaturation. Being more common in vitro, on rare occasions also reported in vivo in association with inflammatory or cystic lesions and confused with parasites or calcification on needle aspirates. The current paper documents that LRs may be seen in noncystic and noninflammatory changes of the breast.